Enhancing Data Security Protocols: An Analysis of Funded Social Service Agencies in Singapore - Mohd Yacob, Azral Bin (Digital Repository of Theses - SSBM Geneva, 2025)
Cybersecurity is a critical concern for funded social service agencies in Singapore, given their responsibility to protect sensitive data while complying with regulatory requirements. This study examines how these agencies implement cybersecurity measures, manage threats, and adhere to regulations under the Personal Data Protection Act (PDPA) and the Cyber Security Act (CSA). The research also evaluates the effectiveness of incident response strategies, employee training programs, and inter-agency collaboration in enhancing cybersecurity resilience. A quantitative research approach was employed, collecting survey data from agency representatives. Statistical analyses, including ANOVA, Pearson correlation, Chi-Square, and regression tests, were conducted to identify variations in cybersecurity preparedness across different agency types. The findings indicate that while most agencies have formal security policies, their implementation is challenged by financial constraints, limited expertise, and regulatory complexities. Larger, well-funded agencies are better equipped to manage cybersecurity risks, while smaller and non-profit agencies struggle with maintaining up-to-date security frameworks. Incident response strategies were found to vary significantly among agencies, with structured plans more common in well-resourced organisations. Employee training emerged as a key factor in reducing security breaches caused by human error, reinforcing the need for continuous education programs. The study also highlights the role of collaboration in strengthening cybersecurity, though concerns about data sensitivity and compliance requirements often limit inter-agency cooperation. The study recommends targeted interventions to enhance cybersecurity resilience in the sector. These include simplifying compliance frameworks, increasing funding support, adopting AI-driven security solutions, and developing structured training programs to mitigate human error. Strengthening partnerships between social service agencies, government bodies, and cybersecurity professionals can facilitate knowledge-sharing and resource optimization. The research contributes to policy discussions on improving cybersecurity measures within the social service sector and underscores the importance of balancing compliance with practical security implementations. Future research should explore emerging cybersecurity threats, long-term impacts of compliance policies, and the effectiveness of evolving security technologies in protecting social service organisations.